Factors Influencing Stakeholders’ Perception Towards Innovation on Halal Management Practices - Md Lezal, Nur Adibah; Anim Zalina Azizan (Research in Management of Technology and Business, 2026)
For this study, the halal industry in Malaysia is growing rapidly due to technological advancements, but the perception of stakeholders is an important factor in the adoption of innovations. For the purpose of this study, to assess factors that influence the perception of stakeholders towards an innovation in the management practices of the halal industry, the proposed framework is guided by the Technology Acceptance Model (TAM), which emphasizes perceived usefulness (PU), perceived ease of use (PEOU), trust (TR), and perceived enjoyment (PE). For the purpose of this study, the population included halal stakeholders in the state of Malacca, and the sampling technique involved the use of a cross-sectional survey of 161 respondents, consisting of managers (38.5%) as well as halal executives, compliance, and the internal halal committees, employing an organized 5-point likert-scale validated questionnaire that had undergone the process of pilot-testing, showing strong reliability (Cronbach’s alpha = 0.957). The important findings indicate strong perception levels of the constructs PU (Mean = 4.50, SD = 0.69), TR (Mean = 4.62, SD = 0.52), and the total perception of the stakeholders towards innovation (SPI, Mean = 4.58, SD = 0.58), with the dominance of the positive factors of PU and TR being evident. Notably, these findings emphasize the intervening significance of training and the user-friendly approach for boosting the adoption rate, providing useful interpretations for JAKIM, Malaysia’s halal authorities, to position the country as the world’s halal hub.